ALK and ROS1 rearrangements tested by fluorescence in situ hybridization in cytological smears from advanced non‐small cell lung cancer patients. Issue 11 (7th July 2015) - Bozzetti, Cecilia; Nizzoli, Rita; Tiseo, Marcello; Squadrilli, Anna; Lagrasta, Costanza; Buti, Sebastiano; Gasparro, Donatello; Zanoni, Daniele; Majori, Maria; De Filippo, Massimo; Mazzoni, Francesca; Maddau, Cristina; et al.
<x xml:space="preserve">Abstract</x> Background The identification of ALK and ROS1 rearrangements and the availability of an effective target therapy, such as crizotinib, represent a new option in the treatment of advanced non‐small cell lung cancer (NSCLC) patients. In light of recent advances in non‐invasive diagnostic procedures, we aimed to demonstrate that direct cytological smears are suitable for assessing ALK and ROS1 rearrangements in patients with NSCLC. Methods Fifty‐five patients with a cytological diagnosis of lung adenocarcinoma (ADC) were evaluated for ALK rearrangements by fluorescence in situ hybridization (FISH) and 12 patients for ROS1 FISH rearrangements. Seventeen of the 55 cytological samples tested for ALK were obtained from the primary tumor and 38 from metastatic lesions. Ten of 12 samples evaluated for ROS1 were obtained from metastatic sites and two from the primary tumor. Results ALK FISH was successful in 49/55 (89%) cytological ADC samples and ROS1 FISH in all 12 cytological samples. ALK rearrangements were found in 3/13 (23%) primary tumors and 7/36 (19%) metastatic sites. ROS1 rearrangements were found in one of the two primary tumors and in two of the 10 metastases. Two of the three rearranged cases were tested on cytology after knowing that they were rearranged on histology in order to increase representativeness of ROS1 rearranged cases in this study. Conclusion Whenever cytology represents the only available material for diagnosis and biological characterization of NSCLC, minimally invasive procedures may provide an additional important source of cellular material for FISH assessment of ALK and ROS1 rearrangements.//// Diagn. Cytopathol. 2015;43:941–946. © 2015 Wiley Periodicals, Inc.